Strategi Pengembangan Usaha Budidaya Ikan Nila (Oreochromis niloticus) di Desa Sukamantri, Kecamatan Tamansari, Kabupaten Bogor - Ilham Galeh Ramadhan; Aliffia Anassyahtira Hamzah; Camelia Trirahmawati; Apan Sopian; Ratu Nabilla Rahmawati; Muhammad Radithya Naufal Apriansyah; Dian Eka Ramadhani; Sarah Anjani; Sofia Deannisa (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2024)
Red tilapia (Oreochromis niloticus) is a freshwater fish known for its high tolerance to environmental conditions, low water quality, and ability to adapt well to various situations. Data from the Ministry of Marine Affairs and Fisheries shows that tilapia production in Indonesia has increased significantly, from 1,172,633.38 kg in 2020 to 1,300,529.23 kilograms in 2021, with a percentage increase of 10.90%. The community strongly influences the local economy and food security. Tilapia farming is widely chosen because it has a stable selling price and fast growth. Many farmers have chosen Tilapia farming as their primary source of livelihood. This research aimed to study the socio-economic conditions, difficulties, and development opportunities of tilapia farming in the community. The results show that although this business contributes significantly to family income, there are several constraints, such as fluctuating market prices, limited access to technology, and low aquaculture skills. In addition, the success of aquaculture is also affected by environmental conditions and resource availability. Therefore, a development plan that includes training, access to capital, and improved infrastructure is needed to improve yields and the welfare of the tilapia farming community.